Sistem Automatic Transfer Switch (ATS) Terintegrasi PLN-Panel Surya Berbasis Time Delay Relay (TDR) untuk Beban Ruang Praktik Siswa - Mohammad Wahyudin; Edy Sumarno; Sunardi Sunardi; Kartika Sekarsari (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
The availability of electrical energy is one of the important factors during learning activities. However, because the electrical system can be said to be very complicated, starting from the generator center all the way to the consumer, there will most likely be a disruption that causes the flow of power to the consumer to be cut off. One of the factors that affect includes environmental factors, maintenance and other factors, so that the learning process is slightly hampered. The purpose of this research is to maintain electricity supply by automatically switching sources and utilizing renewable energy as a reserve for lighting students' practice rooms. Therefore, a system is needed that automatically regulates the switching of primary sources to backup sources. Automatic Transfer Switch or ATS is a device that automatically switches the main power source from PLN to a backup source such as solar panels by setting the time using Time Delay Relay (TDR). TDR functions to regulate the duration of the power source change operation to meet load needs, especially on small loads such as student practice rooms with a voltage of 220 Volts in one language. The advantage of this system is that it is able to automatically switch electricity supply between PLN and Solar Panels with a controlled time lag. The research method involves the installation of electrical panels and Solar Panels using Solar Charger Controller or SCC, Inverter devices. At the time of the study, the adjustment of the TDR setting to set the time lag on the ATS. SCC settings are carried out to obtain Inputs and Outputs in the optimal battery charging process where the measurement results show that When the load of the incandescent lamp is increased from 50Watt to 300Watt, the current increases from 4.47A to 25.2A, while the voltage decreases from 11.7V to 9.8V. In conclusion, the greater the load, the solar panel voltage decreases and the current increases. The results of the study show that the implementation of the automatic transfer switch system is able to automatically switch the electricity supply between PLN and Solar Panels with a controlled time lag.